Konsep Dakwah Rahmatan Lil 'Alamin dalam Pemikiran Tokoh Modern Islam: Analisis Komparatif Pemikiran Nurcholish Madjid dan Abdurrahman Wahid - Tsania, Rahma Zulfa; Rahma Zulfa (IKHBAR: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This abstract summarizes the essence of the research, including the objectives, methods, main findings, and conclusions. The focus is on how Nurcholish Madjid (Cak Nur) and Abdurrahman Wahid (Gus Dur) interpret and apply the concept of da'wah rahmatan lil 'alamin (mercy for the universe). This research aims to analyze the similarities and differences in the thinking of these two figures, as well as their implications for da'wah practices in Indonesia. Using a qualitative-comparative approach, this article shows that although both adhere to an inclusive and moderate vision of Islam, there are nuances in the emphasis and implementation of the concept of rahmatan lil 'alamin in the context of pluralism and modernity. Cak Nur focuses on rationality and the demythologization of religion, while Gus Dur emphasizes humanism and the indigenization of Islam. These findings contribute to a richer understanding of modern Islamic discourse in Indonesia and its relevance for strengthening harmonious coexistence.